Evaluation of the effect of Lactobacillus reuteri V3401 on biomarkers of inflammation, cardiovascular risk and liver steatosis in obese adults with metabolic syndrome: a randomized clinical trial (PROSIR) - Carmen Tenorio-Jiménez; María José Martínez-Ramírez; Mercedes Tercero-Lozano; Carmen Arraiza-Irigoyen; Isabel Del Castillo-Codes; Josune Olza; Julio Plaza-Díaz; Luis Fontana; Jairo H. Migueles; Mónica Olivares; Ángel Gil; Carolina Gomez-Llorente (BMC, 2018)
Abstract Background Obesity is characterized by increased fat mass and is associated with the development of insulin resistance syndrome (IRS), usually known as metabolic syndrome. The alteration of the intestinal microbiota composition has a role in the development of IRS associated with obesity, and probiotics, which are live microorganisms that confer a health benefit to the host, contribute to restore intestinal microbiota homeostasis and lower peripheral tissue insulin resistance. We aim to evaluate the effects of the probiotic strain Lactobacillus reuteri (L. reuteri) V3401 on the composition of intestinal microbiota, markers of insulin resistance and biomarkers of inflammation, cardiovascular risk, and hepatic steatosis in patients with overweight and obesity exhibiting IRS. Methods/design We describe a randomized, double-blind, crossover, placebo-controlled, and single-centre trial. Sixty participants (aged 18 to 65 years) diagnosed with IRS will be randomized in a 1:1 ratio to receive either a daily dose of placebo or 5 × 109 colony-forming units of L. reuteri V3401. The study will consist of two intervention periods of 12 weeks separated by a washout period of 6 weeks and preceded by another washout period of 2 weeks. The primary outcome will be the change in plasma lipopolysaccharide (LPS) levels at 12 weeks. Secondary outcomes will include anthropometric parameters, lipid profile, glucose metabolism, microbiota composition, hepatic steatosis, and inflammatory and cardiovascular biomarkers. Blood and stool samples will be collected at baseline, at the midpoint (only stool samples) and immediately after each intervention period. Luminex technology will be used to measure interleukins. For statistical analysis, a mixed ANOVA model will be employed to calculate changes in the outcome variables. Discussion This is the first time that L. reuteri V3401 will be evaluated in patients with IRS. Therefore, this study will provide valuable scientific information about the effects of this strain in metabolic syndrome patients. Trial registration The trial has been retrospectively registered in ClinicalTrials.gov on the 23rd November 2016 (ID: NCT02972567), during the recruitment phase.